María de la Luz Matus-Mendoza. Linguistic Variation in Mexican Spanish as Spoken in Two Communities –Moroleon, Mexico and Kennett Square, Pennsylvania - Barriga Villanueva, Rebecca (Boletín de Filología, 2004)
Linguistic Variation in Mexican Spanish as Spoken in Two Communities -Moroleon, Mexico and Kennett Square, Pennsylvania. Lewinston, New York, Edwin Mellen Press, 2002, VII + 124 páginas.